Peran Rumah Tahfizh Jaringan Rumah Qur’an Haramain Karangpandan dalam Penyelenggaran Pendidikan Al-Qur’an - Putra, Rizky Pratama; Amrulloh, Muhamad; Saputra, Akhmadiyah (PT. Riset Press International, 2024)
This research discusses the study of the role of tahfizh house network qur'an haramain karangpandan in organizing al-qur'an education with the subject matter of how the role of tahfizh house network qur'an haramain karangpandan in organizing al-qur'an education the role of tahfizh house network qur'an haramain karangpandan in organizing al-qur'an education. The purpose of the research. First, to know the role of tahfizh house in organizing al-qur'an education in children in Karangpandan. Second, want the role of tahfizh house network qur'an haramain karangpandan in organizing al-qur'an education in karangpandan. The method used is qualitative and analytical descriptive.